2017
DOI: 10.3233/cbm-160240
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in esophageal squamous cell carcinoma: Potential biomarkers and therapeutic targets

Abstract: Esophageal cancer is a common cause of cancer-related deaths worldwide. Squamous cell carcinoma (SCC) is the major histological type of esophageal cancer in developing countries including China, and the prognosis is very poor. Many microRNAs are involved in several important biological and pathologic processes, and promote tumorigenesis. To better understand the prognostic and therapeutic roles of microRNAs in ESCC, we reviewed the diagnosis and prognosis associated oncogenic microRNAs (e.g. miR-21 and miR-17-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…In addition, the combination of erlotinib with other agents, showing even greater effects in inhibition of human cancer cells through multiple molecular mechanisms, have also been reported in other studies [54][55][56]. Our findings suggest that ATL-1 might sensitize or enhance the effect of erlotinib in the controlling human lung cancer cell growth or vice versa via targeting the tumor suppressor target genes PDK1 and EZH2 [57], and HOTAIR signaling axis. This implies a potential additive synergy of these agents in EGFR-TKI resistance setting.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the combination of erlotinib with other agents, showing even greater effects in inhibition of human cancer cells through multiple molecular mechanisms, have also been reported in other studies [54][55][56]. Our findings suggest that ATL-1 might sensitize or enhance the effect of erlotinib in the controlling human lung cancer cell growth or vice versa via targeting the tumor suppressor target genes PDK1 and EZH2 [57], and HOTAIR signaling axis. This implies a potential additive synergy of these agents in EGFR-TKI resistance setting.…”
Section: Discussionsupporting
confidence: 84%
“…Several reports point to miRNAs to be involved in Barrett's carcinogenesis 5,6 and in the development of the esophageal squamous cell carcinoma. 7 Recently, Shoji and colleagues performed a miRNA expression profile on esophageal mucosal biopsies from 8 patients with achalasia and 4 healthy volunteers and showed the miRNA-130a highly expressed in patients. 8 In this study, we used miRNA microarrays to identify miRNAs with altered expression in esophageal mucosa of achalasic patients.…”
mentioning
confidence: 99%
“…7,22 There are many serological tumor markers in diagnosing and monitoring the malignant tumors. Furthermore, many studies suggested that the abnormal expression of miRNAs could set off adverse clinical and pathological features 29 and cause the invasion and metastasis of ESCC. [23][24][25] miRNAs are known to play a vital role in the occurrence and development of many malignant tumors, [26][27][28] including ESCC.…”
Section: Discussionmentioning
confidence: 99%